Selected Lectures of the XXIII National Congress of the Italian Society of Neonatology (Società Italiana di Neonatologia, SIN); Milan (Italy); September 25th-28th, 2017 - - (Hygeia Press di Corridori Marinella, 2017)
Selected Lectures of the XXIII National Congress of the Italian Society of Neonatology (Società Italiana di Neonatologia, SIN); Milan (Italy); September 25-28, 2017 Guest Editor: Mauro Stronati LECT 1. COMPLEMENTARY FEEDING IN PRETERM INFANTS: MYTHS AND FACTS • A. Aceti LECT 2. NEONATAL HYDRONEPHROSIS • R. Agostiniani LECT 3. WHEN A NEWBORN DIES IN NICU • M. Susi, S. Dosso, A. Anselmi, A. Bertolini, P. Biban LECT 4. RED REFLEX TESTING IMPLEMENTATION IN THE NURSERY: COMPARING EXPERIENCES • G. Araimo, S.G. Osnaghi, M. Colombo, G. Regiroli, L. Colombo, F. Mosca LECT 5. PAIN MANAGEMENT IN PREMATURE INFANTS. PAIN SEMIOLOGY AND ASSESSMENT. ANALGESIA FOR SKIN BREAKING PROCEDURES • I. Arenga LECT 6. VISUAL EVOKED POTENTIALS: WHY AND WHEN PERFORM THEM • A. Baldascino, G. Amorelli, D. Lepore, F. Molle, G. D'Amico, A. Caporossi LECT 7. NURSING NEONATES SUPPORTED ON ECMO: ORGANIZATIONAL FEATURES AND CARING ASPECTS • C. Baracetti, G. Cavallaro, G. Raffaeli, L. Plevani, F. Mosca LECT 8. NEONATAL HYPO- AND HYPERGLYCEMIA: WHAT TO KNOW, WHAT TO DO • G. Barera, G. Cassano LECT 9. THE ESSENTIAL CARE LEVELS: INDICATIONS FOR THE NEWBORN • S. Battilomo LECT 10. VITAMIN D: OLD AND NEW • A. Boldrini, M. Del Pistoia LECT 11. NURSING-SENSITIVE OUTCOMES IN NEONATOLOGY • L. Boni, G. Gargano LECT 12. REQUIREMENTS OF MACRONUTRIENTS AND MINERALS IN PARENTERAL NUTRITION OF PRETERM INFANTS • V. Bozzetti, P.E. Tagliabue LECT 13. KANGAROO MOTHER CARE (KMC) AND NEUROPROTECTION • G. Calciolari, C. Artese, N. Bertoncelli, E. Beccaria, V. Chiandotto, G. Colombo, S. De Marca, R. Montirosso, G. Paterlini, N. Simeone, F. Ferrari LECT 14. HEMODYNAMIC PRINCIPLES AND MANAGEMENT OF EXTRACORPOREAL MEMBRANE OXYGENATION SUPPORT • F. Canesi, F. Conigliaro, R. Fierro, G. Cavallaro, G. Raffaeli, F. Mosca LECT 15. THE STABILIZATION OF THE NEWBORN BEFORE THE TRANSPORT • V. Cardilli, P. Repole, S. Caoci, R. Cellitti LECT 16. NEONATAL EXTRACORPOREAL MEMBRANE OXYGENATION: THE BASICS • G. Cavallaro, G. Raffaeli, F. Mosca LECT 17. MONITORING THE PRETERM INFANT'S TRANSITION AT BIRTH • F. Cavigioli, I. Bresesti, G. Lista LECT 18. CEREBRAL PRENATAL DAMAGE: WHICH IS THE BURDEN OF INFECTIONS? • R.M. Cerbo, C. Mastropietro, M. Stronati LECT 19. NEONATAL INFECTIONS: RECENT ADVANCES • G. Chirico LECT 20. THE ENGINEER AND THE SINGLE FAMILY ROOM (SFR): THE ALLIANCE WITH THE CLINICIAN • P. Coglianese LECT 21. BREAST MILK FOR THE PRETERM INFANT: THEORY & PRACTICE • R. Davanzo LECT 22. INEQUALITIES AT BIRTH • M. De Curtis, S. Simeoni, L. Frova LECT 23. PHARMACOLOGICAL NEUROPROTECTION • A. Dotta, I. Savarese LECT 24. WHEN AN INFANT DIES IN NEONATAL INTENSIVE CARE UNIT (NICU): EXPERIENCES BY NOVARA AND TURIN • E. Busca, A. Elia LECT 25. THE NEONATAL NETWORK OF THE ITALIAN SOCIETY OF NEONATOLOGY • A. Fabiano, F. Franco, P. Paolillo LECT 26. NEUROPHYSIOLOGICAL TESTS IN THE NEONATAL PERIOD • R. Falsaperla, A. Suppiej, M.A.N. Saporito LECT 27. VENTILATION STRATEGIES FOR CRITICALLY ILL NEONATES WITH BRONCHIOLITIS • T. Fedeli, G. Pomero, P. Papoff, P. Tagliabue LECT 28. UTILIZATION OF ECHOCARDIOGRAPHY AND MANAGEMENT OF PATENT DUCTUS ARTERIOSUS: TWO SURVEYS IN ITALIAN NEONATAL INTENSIVE CARE UNITS • I. Corsini, B. Ficial, S. Fiocchi, F, Schena, I. Capolupo, R.M. Cerbo, M. Condò, D. Doni, S. La Placa, S. Porzio, K. Rossi, S. Salvadori, M. Savoia; the Study Group of Neonatal Cardiology of the Italian Society LECT 29. CRANIAL ULTRASOUND IN LATE PRETERM INFANTS • M. Fumagalli, P. Schiavolin, S. Passera, C. Fontana, F. Mosca LECT 30. CAN REGISTRIES AND HEALTH ADMINISTRATIVE DATA HELP IMPROVE QUALITY OF CARE? • L. Gagliardi LECT 31. POSTNATAL MANAGEMENT OF URINARY TRACT DILATION DETECTED DURING PREGNANCY • R. Galiano, P. Novellino LECT 32. ITALIAN RECOMMENDATIONS FOR THE MANAGEMENT OF CORD CLAMPING IN TERM AND PRETERM NEWBORN • S. Ghirardello LECT 33. NEONATAL ENDOCRINE EMERGENCIES • P. Ghirri, F. Lorenzoni LECT 34. NEONATAL NASAL INTERMITTENT POSITIVE PRESSURE VENTILATION (NIPPV) • C. Gizzi, S. Pesce, R. Lapolla, L. Romaniello, G. Gallicchio, S. De Marca, C. Moretti LECT 35. FAMILY PAEDIATRICIAN'S ROLE IN SUPPORTING BREASTFEEDING • L. Greco LECT 36. PAIN IN NEWBORN AND HOW TO MANAGE IT • P. Lago LECT 37. DELIVERY ROOM MANAGEMENT OF NEWLY BORN INFANT: WHAT TO DO AND NOT TO DO • G. Lista, I. Bresesti LECT 38. ECMO IN NEONATAL TRANSPORT: EXPERIENCE FROM A NORTH EASTERN ITALIAN CENTER • E. Lolli, G. Pennisi, L. Brombin, D. Fichera, F. Zanella, A. Galderisi, N. Doglioni, D. Trevisanuto, P. Lago, E. Baraldi LECT 39. DYSPHAGIA IN THE PRETERM INFANT • S. Longo, M. Stronati LECT 40. CARDIAC EMERGENCIES IN NEONATES AFTER HOSPITAL DISCHARGE • S. Mannarino, G. Corana, A.C. Codazzi, S. Chiapedi LECT 41. ROLE OF OSTEOPATHY IN NEONATOLOGY • A. Manzotti, F. Cerritelli LECT 42. MANAGEMENT OF THE NEWBORN INFANT WITH CONGENITAL ANOMALIES • A. Borghesi, L. Memo LECT 43. UNIVERSAL NEWBORN HEARING SCREENING: RECOMMENDATIONS AND CRITICISMS • C. Morando, G. Conti, G. Araimo, S. Aversa, A. Baldascino, L. Bubbico, W. Buffolano, C. Giannantonio, S. Martinelli; The Sense Organs Study group of the Italian Neonatology Society LECT 44. ALARM MANAGEMENT: A NURSE CHALLENGE IN A SINGLE FAMILY ROOM DESIGNED NEONATAL INTENSIVE CARE UNIT • M. Raso, D. Motta, L. Oricchio, A. Carlucci, A. Battan, P. Sala, V. Galbusera LECT 45. APPARENT LIFE-THREATENING EVENTS AND SUDDEN INFANT DEATH SYNDROME • N. Nassi, G.P. Donzelli, M. Peruzzi, C. Arzilli, G. Liccioli, R. Piumelli LECT 46. VIRAL INFECTIONS: DIAGNOSIS AND THERAPY • F. Natale, B. Bizzarri, V. Cardi, M. De Curtis LECT 47. PRETERM NEWBORNS: CARE AND PARENTAL INVOLVEMENT • S. Orcesi, G. Ariaudo, C. Pisoni, L. Provenzi, M. Moncecchi, S. Spairani, C. Naboni, L. Bollani, U. Balottin, R. Montirosso, M. Stronati LECT 48. POSTDISCHARGE MANAGEMENT OF IRON DEFICIENCY ANEMIA IN PRETERM NEWBORNS • S. Perrone, M. Campisano, M. Landi, G. Buonocore LECT 49. PAIN ASSESSMENT IN NEONATAL INTENSIVE CARE UNIT USING THE EDIN SCALE ADMINISTERED BY INFANTS' PARENTS • T. Pesaresi, E. Baudassi, F. Fabbri, N. Simeone LECT 50. APPROACH TO THE DYSMORPHIC NEWBORN • M. Piccione LECT 51. ORGANIC MILK • S. Picone, P. Paolillo LECT 52. ANALGESIA AND POST-OPERATIVE SEDATION • L. Pieragostini LECT 53. PAIN TREATMENT IN RESPIRATORY DISEASES OF THE NEWBORN. GUIDELINES FOR INTUBATION, MECHANICAL AND NON INVASIVE VENTILATION • A. Pirelli LECT 54. ABDOMINAL ULTRASOUND IN THE NEWBORN • C. Poggiani LECT 55. NEONATAL OSTOMY: GOALS AND PRIORITIES • M. Zicchi, S. Porcu, A.R. Tanca, M. Ubertazzi, M.G. Olzai, M.G. Clemente LECT 56. ACUTE SCROTUM • G. Riccipetitoni, M. Carlucci, S. Costanzo, F. Destro LECT 57. PALLIATIVE CARE PRACTICE IN NEONATOLOGY • C. Romagnoli, P. Papacci, A. Spagnolo, E. Zecca LECT 58. NURSES AND NEAR INFRARED SPECTROSCOPY (NIRS): THE ROLE OF NIRS IN NEONATAL INTENSIVE CARE UNIT • O. Ruocco, C. Romano LECT 59. THE ITALIAN CLINICAL PATHWAY FOR THE MANAGEMENT OF UMBILICAL CORD CLAMPING IN TERM AND PRETERM NEWBORNS • S. Ghirardello, A. Cinotti, M. Di Tommaso, S. Fiocchi, A. Locatelli, D. Merazzi, B. Perrone, S. Pratesi, P. Saracco LECT 60. NEONATOLOGIST PERFORMED ECHOCARDIOGRAPHY (NPE): THE ITALIAN PROJECT • M. Savoia, I. Corsini, S. Fiocchi, S. La Placa, S. Porzio, K. Rossi, S. Salvadori, B. Ficial, F. Schena, I. Capolupo, R.M. Cerbo, M. Condò, D. Doni; the Study Group of Neonatal Cardiology of the Italian Society of Neonatology LECT 61. ROLE OF CEREBRAL ULTRASOUND IN PERINATAL STROKE • A. Scoppa LECT 62. FETAL ORIGINS OF HYPERTENSION AND CHRONIC KIDNEY DISEASE • M. Somaschini, D. Manfellotto, G. Remuzzi LECT 63. MOTHERS' KNOWLEDGE AND ATTITUDES TOWARD MEDICATIONS AND NATURAL PRODUCTS USE IN BREASTFEEDING: AN OBSERVATIONAL STUDY IN A TERTIARY CARE UNIVERSITY HOSPITAL OF NORTHERN ITALY • G. Sorrentino, D. Bertocchi, M.E. Bettinelli, E. Bezze, P. Sannino, L. Plevani, F. Mosca LECT 64. UNIVERSAL CONGENITAL CYTOMEGALOVIRUS INFECTION SCREENING USING SALIVA SAMPLES: A SINGLE CENTER EXPERIENCE • V. Spinoni, S. Fiorentini, M.G. Barezzani, A. Raiti, S. Bettelli, P, Accorsi, P. Martelli, T. Bazzana, A. Caruso, G. Chirico LECT 65. THE NURSING ROLE IN CLINICAL TRIALS AND PHARMACOLOGICAL RESEARCH • V. Strini LECT 66. SUPPORTING PREMATURE BABIES AFTER CLINICAL STABILIZATION IN SINGLE FAMILY ROOMS 24/24 H • M. Trevisan, L.